Max Schmidt en el Mato Grosso - Bossert, Federico (2019)
Between 1899 and 1929, Max Schmidt worked for the Berlin Ethnological Museum and undertook three expeditions to the Mato Grosso in order to continue the investigations of his mentor Karl von der Steinen. Between 1900 and 1901 he explored the upper Xingu trying to reach Kamaiurá territory, meeting several Bacairí, Nahukuá and Aweti Indians, and also the Guató of the swamps of upper Paraguay. In 1910 he attended the International Congress of Americanists in Buenos Aires and seized the opportunity to study the Paresí. Between 1926 and 1928 he undertook a final voyage to the upper Xingu and visited the Bacairí, Kaiabi, Paresí, Iranches and Umotinas. In these trips Schmidt took dozens of pictures that document indigenous life and the first interethnic contacts. The paper presents the ethnographic context of these pictures discussing the incidents of each journey, reported in detailed travelogues; the exploration and conquest of the indigenous Mato Grosso by State agents and rubber barons; the ethnographic and methodological heritage of Adolf Bastian, Karl von der Steinen and the ongoing discussion in German ethnology, and Schmidt’s own theoretical and museographical interests. Finally it discusses Schmidt’s ethnographic fieldwork and the role photography played in it.